Role of Difucosylated Lewis Y Antigen in Outcome of Locally Advanced Cervical Squamous Cell Carcinoma Treated with Cisplatin Regimen. Issue 3 (July 2016) - Leone, Julieta; Perez, Juan E.; Dominguez, Maria E.; Iturbe, Julian; Leone, José P.; Mac Donnell, Maria C.; Grosman, Gabriel; Vallejo, Carlos T.; Leone, Bernardo A.; Zwenger, Ariel O.
Background: Several mechanisms are involved in the development of resistance to therapy in locally advanced cervical squamous cell carcinoma (LACSCC). Studies have shown that CD44 and Lewis Y antigen (LeY) form a complex that is associated with chemoresistance, tumor invasion and metastasis. We assessed the role of CD44 and LeY in the outcome of LACSCC patients treated with different chemotherapy regimens. Methods: 126 LACSCC patients at FIGO stages IIB-IVA were selected from the GOCS database: 74 patients included in 3 different prospective phase II trials in the neoadjuvant setting (vinorelbine, docetaxel, ifosfamide-vinorelbine-cisplatin) and 52 patients treated with standard radiochemotherapy based on cisplatin (RCBC). Clinical data at baseline, disease-free survival (DFS) and overall survival (OS) were recorded. Univariate and multivariate Cox models were employed. Results: Median age was 45.6 years (range: 24.9-80.5). Sixty-three and 47 tumors were CD44+ and LeY+, respectively. Tumors with expansive growth showed higher grade (p = 0.0024), mitotic index (p = 0.0505), tumor necrosis (p = 0.0191), LeY+ (p = 0.0034) and CD44+/LeY+ coexpression (p = 0.0334). CD44+ cells were present in 91.3% of patients with local recurrence (p = 0.0317). Advanced stage was associated with LeY+ tumors. Patients treated with RCBC had worse DFS and OS when their tumors expressed LeY (p = 0.0083 and p = 0.0137, respectively). Pre-treatment hemoglobin level, FIGO stage and tumor response remained the most significant prognostic factors in Cox regression. Conclusions: In our cohort of LACSCC patients, the coexpression of CD44 and LeY was not associated with worse outcome. However, in the subgroup of patients receiving RCBC, LeY expression was correlated with shorter DFS and OS.